الألعاب اللغوية في فلسفة فتشغنشتاين - يوسف, تومي جويدة (جامعة الوادي - University of Eloued, 2022)
المفكر النمساوي فتشغنشتاين أحد مؤسسي الفلسفة التحليليّة ، معتبرا اللغة واصفة للواقع . في حين اُتخذت أعماله كمناهج تُدرس في الجامعات في ذلك الوقت ، كان ل.ف يمحص أفكاره بتحوير رؤيته اتجاه اللغة ، متداركا خطأ اعْتِبَارِها واصفة فهو تضييق لقدراتها الخلاقة . يسعى هذا البحث لفتح نافذة على فلسفة ل.ف "في مرحلته الثانيّة"، مركزا على مفهوم " التشابه الأسري" Abstract: The Austrian thinker wittgenstein, one of the founders of the analytical philosophy, considering language a description of reality. While his thoughts were adopted as curricula, taught in universities at that time, Wittgenstein was scrutinizing his thoughts, by changing his view towards language, rectifying thus the mistake of considering it descriptive, which constitutes a limitation of its creative capabilities. This research aims at shedding light on wittgenstein’s philosophy in his “second phase”, with a focus on the concept “Family Resemblance
مقال
Keywords: analytical philosophy; Language Games; Family Resemblance ; philosophy; wittgenstein. ; analytical philosophy ; Language Games ; Family Resemblance ; analytical philosophy; Language Games; Family Resemblance ; philosophy; wittgenstein. ; philosophy; الألعاب اللغوية ; التشابه الأسري ; فلسفة ; فتشغنشتاين